2020
DOI: 10.3390/w13010044
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Behaviour of Extensive Green Roofs with Native Plants in the Humid Subtropical Climate Context

Abstract: Different mitigation measures with vegetation have been proposed to sustainably manage rainwater, among which green roofs have demonstrated to be a valid solution in urbanized areas. Green roofs have gained interest also in Italy, but their spreading is generally based on application of ready-to-use packages, poorly tested in the specific climate conditions. A study was carried out to evaluate the green roof solution most suitable in the humid, subtropical climate context of Veneto Plain (north-eastern Italy) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Along the same line, Rosatto et al 2015 [45] described a decrease in storage capacity of the studied extensive GRs (15 cm media depth) (from 68% to 16%) with increasing precipitation intensity (ranging from 21 mm to over 90 mm precipitation events). Results presented by Bortolini et al 2021 [46] once again corroborated that GR systems present a high capacity to retain precipitation, with retained rainfall volumes varying depending on the intensity of the events: ≈100% for light precipitation (<10 mm); 48-95% for medium precipitation (≥10 and <25 mm) and 20-88% for heavy precipitation (≥25 mm). This differences in retention capacity not only depends on the amount of precipitation (rainfall depth) but also on the weather conditions before the event occurs.…”
Section: A Climate Variables -Event Intensity/durationmentioning
confidence: 66%
See 1 more Smart Citation
“…Along the same line, Rosatto et al 2015 [45] described a decrease in storage capacity of the studied extensive GRs (15 cm media depth) (from 68% to 16%) with increasing precipitation intensity (ranging from 21 mm to over 90 mm precipitation events). Results presented by Bortolini et al 2021 [46] once again corroborated that GR systems present a high capacity to retain precipitation, with retained rainfall volumes varying depending on the intensity of the events: ≈100% for light precipitation (<10 mm); 48-95% for medium precipitation (≥10 and <25 mm) and 20-88% for heavy precipitation (≥25 mm). This differences in retention capacity not only depends on the amount of precipitation (rainfall depth) but also on the weather conditions before the event occurs.…”
Section: A Climate Variables -Event Intensity/durationmentioning
confidence: 66%
“…Baryla et al 2018 [55] concluded that GR substrates with a mixture of mineral and organic materials in their composition showed higher retention abilities compared to growing substrates composed of only mineral materials. On the other hand, Bortolini et al 2021 [46] described a GR holding capacity between 46.2% and 62.9% against 15.4% retention by gravel. Another study reported that a substrate layer composed of fine tile duplicated the capacity to retain rainwater compared to the same substrate layer composed of coarse tile [38].…”
Section: B Gr Physical Features/design Variablesmentioning
confidence: 99%
“…A multi-year study conducted in Veneto (Bortolini and Zanin, 2018) has shown that a bioretention area with ornamental herbaceous plants (rain garden) with a surface equal to 10% of a drainage area (a building roof) can manage more than 95% of the total runoff, throughout infiltration and evapotranspiration, effectively avoiding also irrigation request during the summer periods. In another study conducted in the same area, Bortolini et al (2021) highlighted the positive effect on runoff reduction of various extensive green roof solutions. Depending on the stratigraphy and the type of vegetation, the reduction in runoff can exceed on average over 60% in the year, even if the effectiveness is less during the most intense rainy events, especially in periods characterized by lower temperatures in which the evapotranspiration phenomena are reduced (from November to February).…”
Section: Introductionmentioning
confidence: 93%
“…In a subtropical climate in northeastern Italy, ref. [50] constructed 36 platforms raised 1000 mm (3.3 ft) above ground for a full surface area of 0.44 m 2 for two years (2014-2016). The objective was to investigate the effect of different vegetation types (herbaceous perennial (HE), Sedum (SE), and suffruticose (SF)), substrate types (120 mm in depth volcanic substrate (VS), 120 mm in depth recycled substrate (RS)), and drainage (PL)/storage layers (ML) on the hydrological performance of GR.…”
Section: The Influence Of Gr System Characteristicmentioning
confidence: 99%